Qualitative Study of Efforts to Prevent Fabrication and Falsification of Research Data of Yogyakarta Midwifery Students - Suci Fitriana Pramudya Wardani; Amrina Nur Rohmah; Ayu Aminatussyadiah (Jurnal Kebidanan, 2024)
Midwifery education requires midwifery students to be able to conduct research to develop the knowledge they have received and to support community service, but there are still many mistakes that occur in research such as fabrication, falsification and plagiarism. This research was conducted to find out the efforts made by the institution in preventing the fabrication and falsification of data for students of Diploma IV Midwifery Program in Yogyakarta. This research is a qualitative research using a narrative study approach. Data collection in this study used semi-structured interviews. This research was conducted with 8 informants including the Head of the Quality Assurance Agency of the Study Program, Head of Study Program, Quality Assurance Department, the Head of the Study Program, Thesis Coordinator and five lecturers of Diploma IV Midwifery Program in Yogyakarta. Efforts to prevent and overcome fabrication, falsification and plagiarism are carried out from the mentoring stage until the trial takes place, starting from the supervising lecturer, thesis coordinator, to the examining lecturer during the thesis examination, and there has been no written sanction given to students related to the fabrication and falsification of research data. Fabrication and falsification of data will result in wrong research so that it will create wrong knowledge as well.